Limited Index of Clinical Suspicion and Underdiagnosis of Histopathologically Documented Invasive Mold Infections. (2nd April 2021) - Caudron de Coquereaumont, Grégoire; Couchepin, Jade; Perentes, Jean Y; Krueger, Thorsten; Lovis, Alban; Rotman, Samuel; Lamoth, Frederic
Abstract: Invasive mold infections (IMIs) are difficult to diagnose. This analysis of histopathologically proven IMIs at our institution (2010–2019) showed that 11/41 (27%) of them were not suspected at the time of biopsy/autopsy (9/17, 53% among autopsies). The rate of missed diagnosis was particularly high (8/16, 50%) among nonhematologic cancer patients.